Dynamic evolution control of bidirectional converter for interfacing ultracapacitor to fuel cell [electronic resource] - 197198 Ahmad Saudi Samosir; Fakulti Kejuruteraan Elektrik (2010)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2010